Polymyalgia rheumatica in a melanoma patient 11 months after completion of immunotherapy with nivolumab. Issue 3 (6th April 2020) - Lobo, Yolanka; Good, Phillip; Murphy, Felicity
Abstract: Background: Immune checkpoint inhibitor (ICI) therapy has revolutionised the treatment of several cancers but can also lead to the development of immune‐related adverse effects including dermatologic, gastrointestinal, endocrine, hepatic, pulmonary and less commonly, rheumatic toxicities. Toxicities associated with ICI therapy can occur several months or even years after initiation. Case reports of polymyalgia rheumatica (PMR) associated with nivolumab use are rare. We herein describe, for the first time, a case of PMR in a melanoma patient after cessation of treatment with nivolumab. Case: An 88‐year‐old man with a history of stage IV M1c BRAF wild‐type melanoma presented with a 1 month history of arthralgias and morning stiffness, predominantly affecting the shoulders and hips, associated with fatigue and weight loss. He had undergone wide local excision of a primary malignant melanoma in the left buttock region several years prior. Immunotherapy with nivolumab was initiated following disease relapse with multiple metastases. Nivolumab was discontinued due to demonstration of complete metabolic response on serial positron emission and computed tomography scans. Symptoms appeared 11 months after completion of treatment. A diagnosis of PMR was made and treatment with oral prednisone was initiated leading to complete resolution of symptoms within 1 week. We believe that the development of PMR in our patient was likely precipitated by nivolumab. Conclusion: This case demonstrates that PMR, although rare, may occur as an adverse effect both during and after treatment with nivolumab, leading to disabling symptoms and poor quality of life. Prompt diagnosis is crucial to enable timely commencement of corticosteroid therapy in order to avoid further impact on morbidity and mortality for cancer patients. This case highlights the importance of prompt referral to rheumatology, as well as the need for close collaboration between oncologists and rheumatologists to accurately diagnose and successfully manage these patients.